Nucleotide Manipulatives to Illustrate the Central Dogma - Sonja B. Yung (American Society for Microbiology, 2015)
The central dogma is a core concept that is critical for introductory biology and microbiology students to master. However, students often struggle to conceptualize the processes involved, and fail to move beyond simply memorizing the basic facts. To encourage critical thinking, we have designed a set of magnetic nucleotide manipulatives that allow students to model DNA structure, along with the processes of replication, transcription, and translation.